The Genomic Architecture of Fowl Typhoid Resistance in Commercial Layers - Psifidi, Androniki; Russell, Kay M.; Matika, Oswald; Sánchez-Molano, Enrique; Wigley, Paul; Fulton, Janet E.; Stevens, Mark P.; Fife, Mark S. (Frontiers in Genetics, 2018)
Salmonella enterica serovar Gallinarum causes devastating outbreaks of fowl typhoid across the globe, especially in developing countries. With the use of antimicrobial agents being reduced due to legislation and the absence of licensed vaccines in some parts of the world, an attractive complementary control strategy is to breed chickens for increased resistance to Salmonella. The potential for genetic control of salmonellosis has been demonstrated by experimental challenge of inbred populations. Quantitative trait loci (QTL) associated with resistance have been identified in many genomic regions. A major QTL associated with systemic salmonellosis has been identified in a region termed SAL1. In the present study, two outbreaks of fowl typhoid in 2007 and 2011 in the UK were used to investigate the genetic architecture of Salmonella resistance in commercial laying hens. In the first outbreak 100 resistant and 150 susceptible layers were genotyped using 11 single nucleotide polymorphism (SNP) and 3 microsatellite markers located in the previously identified SAL1 region on chromosome 5. From the second outbreak 100 resistant and 200 susceptible layers, belonging to a different line, were genotyped with a high-density (600K) genome-wide SNP array. Substantial heritability estimates were obtained in both populations (h2=0.22 and 0.26, for the layers in the first and second outbreak, respectively). Significant associations with three markers on chromosome 5 located close to AKT1 and SIVA1 genes, coding for RAC-alpha serine/threonine protein kinase, and the CD27-binding protein Siva1, respectively, were identified in the first outbreak. From analysis of the second outbreak, eight genome-wide significant associations with Salmonella resistance were identified on chromosomes 1, 6, 7, 11, 23, 24, 26, 28 and several others with suggestive genome-wide significance were found. Pathway and network analysis revealed the presence of many innate immune pathways related to Salmonella resistance. Although, significant associations with SNPs located in the SAL1 locus were not identified by the genome-wide scan for layers from the second outbreak, pathway analysis revealed P13K/AKT signalling as the most significant pathway. In summary, resistance to fowl typhoid is a heritable polygenic trait that could possibly be enhanced through selective breeding.